The black book of buried secrets - Kass, Mallory; Riordan, Rick. (New York : Scholastic, 2010)
"The Black Book of Buried Secrets" lays bare each hidden fact, concealed strategy, top agent, lost founder, secret base and hushed-up scandal of the Clue hunt. This complete guide to the Cahills contains information on all five branches, including the notoriously elusive Madrigals.
Keywords: Brothers and sisters -- Juvenile fiction; Orphans -- Juvenile fiction; Inheritance and succession -- Juvenile fiction; Adventure stories; Code and cipher stories